Implementation of Active Learning Strategies in Islamic Religious Education for Primary School Students - Arifin, Zainul; Febriani, Afifah; Maihendra, Maihendra; Az-zahra, Dwi Wahyuni (Khalaqa: Journal of Education and Learning, 2024)
The implementation of the Merdeka Belajar Curriculum in Islamic Religious Education (IRE) faces several challenges, particularly in planning, execution, and evaluation. These issues are evident in the teaching process, where components such as the ATP/Syllabus and Teaching Module/RPP are not optimally utilized, resulting in low student engagement during lessons. This study aims to identify the problems encountered in planning, implementing, and evaluating the curriculum in IRE subjects, as well as to explore teachers’ efforts to address these challenges. Using a qualitative descriptive approach, this field research involved elementary school principals, IRE teachers, other subject teachers, and students as data sources. Data were collected through observation, interviews, and documentation. The findings reveal key issues in planning, such as difficulties in developing ATPs and teaching modules and in implementation, including ineffective use of teaching methods, media, and technology. To overcome these challenges, teachers have introduced various evaluation strategies to improve learning outcomes in elementary schools.